Negociação, Cooperação e Desenvolvimento Local sob uma Perspectiva Sistêmica. Um Estudo de Caso no Arranjo Produtivo Local de Fruticultura de Jaíba-MG - Márcia Freire de Oliveira (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2014)
The purpose of this article is to analyze, from a systemic perspective, how negotiation influences the process of cooperation and if this process contributes with the promotion of local development in regions where local productive arrangements are installed. To achieve this purpose a qualitative and exploratory case study was conducted in the APL of fruit culture in Jaiba-MG. The collection of data was performed using semi-structured interviews in rural properties and institutions that support the APL. The data was analyzed using the technique of content analysis. The results show that the cooperation actions established in APL are mainly multilateral horizontal type, derived from win-win negotiations. These actions contributed to the local development of the APL, above all in the following aspects: training of human resources; improvement of environmental aspects: gaining new customers / market expansion; cost reduction and; improvement of production technology.